Pengembangan Modul Projek Penguatan Profil Pelajar Pancasila Berbasis Muatan Lokal Batik pada Dimensi Kreatif Untuk Anak Usia Dini di TK Islam Miftahul Jannah Semarang - Setyani, Nuza Hery; Sagala, Anita Chandra Dewi; Sulianto, Joko (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2025)
This research aims to develop and implement a project module that is effective in increasing the creativity of early childhood by strengthening the profile of Pancasila students with local batik content. The local batik content taken is Semarangan batik. This module is designed to develop children's creative dimensions, as well as integrating the values of mutual cooperation and cultural diversity. The research method uses RnD (Research and Development), with class B4 subjects at Miftahul Jannah Islamic Kindergarten - Semarang with data collection techniques using observation, interviews, documentation, questionnaires and research instruments. Module development refers to the ADDIE model, involving experts and kindergarten teachers. This module consists of a series of project activities that combine traditional batik techniques with the exploration of children's creative ideas. The implementation of the module was carried out within a period of 6 days in group B at the Miftahul Jannah Islamic Kindergarten, Semarang. Data regarding children's creativity is collected through participatory observation, documentation of children's work, and performance assessments. The research results showed a significant increase in the aspects of fluency and originality in children's works after participating in the P5 Batik Semarangan activities. Apart from that, the children also showed increased ability to collaborate and appreciate cultural diversity through joint batik activities in Semarang. This project module has proven effective in developing creativity in early childhood while fostering Pancasila values. The implementation of this module makes a positive contribution to preserving batik culture and developing children's character from an early age.